The role of connexins in wound healing and repair: novel therapeutic approaches - Jeremy Wong (Frontiers in Physiology, 2016)
Gap junctions are intercellular proteins responsible for mediating both electrical and biochemical coupling through the exchange of ions, second messengers and small metabolites. They are made of two connexons, with each (one) connexon supplied by each cell. A connexon consists of a hexamer of connexins with m. More than 20 connexin isoforms have been described in the literature thus far. Connexins have a short half-life, and therefore gap junction remodelling constantly occurs with a high turnover rate. Connexins undergo post-translational modification, such as phosphorylation, which can modify their channel activities. In this article, the roles of connexins in wound healing and repair are explored. We also consider nNovel strategies for modulating the function or expression of connexins, such as the use of antisense technology, synthetic mimetic peptides and bioactive materials, for the treatment of skin wounds, diabetic and pressure ulcers as well as cornea wounds. are considered.